Relationship Between Effective Dose, Alternative Metrics, and SSDE: Experiences with Two CT Dose-Monitoring Systems - Lilla Szatmáriné Egeresi; László Urbán; Zsolt Dankó; Ervin Balázs; Ervin Berényi; Mária Marosi; János Kiss; Péter Bágyi; Zita Képes; Miklós Emri; László Balkay (Diagnostics, 2025)
Background: We assessed the frequency and causes of discrepancies in CT dose indices such as dose-length product (DLP), size-specific dose estimate (SSDE), and effective dose (ED), as calculated by CT dose-monitoring systems. Our secondary aim was to demonstrate the estimation of size-specific ED (SED) from the patients’ dose records. Methods: The retrospective study included dosimetric data of 79,383 consecutive CT exams performed on two CT scanners. The following dose values were recorded from both the locally developed dose-monitoring system (DMS) and a commercial dose-monitoring program (DWTM): DLP, SSDE, and ED. Only the DMS provided bodyweight-corrected effective dose (SEDDMS) and the SED based on previous published data. Results: Without body-region-specific analysis, there were no tendentious differences between the DLP, ED, or SSDE values obtained from DWTM and DMS. However, the body region-based correlation revealed substantial differences between EDDMS and EDDW, primarily related to inadequate identification of the body. SSDE showed strong correlation to each anatomical category and CT device, except for the head region, where inadequate consideration of CT inclination was the reason for the biased SSDEDW value. Furthermore, by analyzing the SEDDMS, SSDE, and SED correlations, we concluded that SEDDMS is a promising figure for estimating the SED value. Conclusions: SED provides suitable supplementary size-specific dose data to SDDE and may be a preferable choice for estimating cumulative doses in routine radiological practice.